Políticas de avaliação da educação superior no Brasil de FHC a Lula: uma análise crítica dos seus pressupostos e fundamentos - Maria Denise Guedes; Maria Aparecida Segatto Muranaka; José Euzébio de Oliveira Souza Aragão (Centro Universitário Salesiano de São Paulo, 2016)
This paper analyzes public policy evaluation of higher education in Brazil in the government of Fernando Henrique Cardoso and Luiz Inacio Lula da Silva. It aims to present the analysis of the assumptions and theoretical and me-thodological foundations underlying these policies in recent decades, taking the evaluation of Brazilian higher education as a phenomenal expression of multiple relationships of the concrete reality of contemporary capitalist society. Methodologically, from bibliographical and documentary research, analysis is anchored on the assumptions of materialism-dialectical and historical, according to which real data do not appear to man, at first sight, in its concrete form, but as a chaotic representation of whole, showing the phenomenon in its appearance and hiding its essence. Such analyzes have concluded that public policy evaluation for Brazilian higher education, implemented by these governments since the 1990s, has the "Competence Model" as the foundation, which aims to meet the demands of the market for a new profile worker, able to adapt to technical and ideological needs of capital in contemporary society.